Faktor-Faktor Penyebab Pending Klaim Peserta Jaminan Kesehatan Nasional di Rumah Sakit Pusat Pertamina - Meiningtyas, Ayu; Cahya Maulina, Fresty (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2025)
Health financing is an important part in the implementation of the National Health Insurance (JKN), pending claims will cause late payment of claims from BPJS Health to hospitals and harm the hospital's finances and result in delays in paying for medical services for doctors and other health care services. Several factors that cause pending claims are the accuracy of the diagnosis code, the completeness of the medical resume, the completeness of the medical support reports and the completeness of the claim file. This study was conducted to analyze the relationship of each independent variable to the dependent variable. This research is a quantitative research using a cross sectional design. The population in this study were 294 claim files for national health insurance participants with a sample size of 170 files. Data was collected using a checklist sheet, with data analysis techniques using univariate and bivariate analysis with chi square test. The results of the study explained that as many as 40% of pending claim files with the percentage of each independent variable coding accuracy of 87.6%, completeness of medical resumes 95.3%, completeness of medical support 92.3% and completeness of administrative files 84.7%.